The Impact of Globalization, Trade Openness and Economic Growth on Financial Development the Case of Turkey - Hamzehei, Salar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This research has investigated the impact of trade openness, economic growth, and globalization on the financial development of Turkey. The analysis was applied on time series data from the period of 1980 to 2015 using different time series methodologies. First, the data was summarized and explored through descriptive statistics. Afterwards, unit root tests (Augmented Dickey Fuller and Phillips Perron), Johansen cointegration test, vector error correction model (VECM), and Granger causality under VECM were applied on the data. Results show that trade openness, globalization, and economic growth are key determinants of financial development in the case of Turkey and have positive significant relationship with it. To achieve the financial development in Turkey, Turkish government should stabilize its economy to have higher trade openness and globalization Keywords: Financial development, Economic growth, Globalization, Trade openness.

ÖZ: Bu araştırma Türkiye’nin finansal gelişiminde 1980-2015 yılları arasında, ticari açıklığın, ekonomik büyümenin ve globalleşmenin etkilerini araştırmaktadır. İlk olarak, tanımlayıcı istatistikler kullanılarak veriler özetlenmiştir. Daha sonra, verilere birim kök testleri (Augmented Dickey Fuller ve Phillips Perron), Johansen eştümleşme testi, vektör hata düzeltme modeli, ve Granger nedensellik testleri uygulanmıştır. Elde edilen sonuçlar ticari açıklık, globalleşme ve ekonomik büyüme Türkiye’deki finansal gelişimin uzun dönemli belirleyicileridir. Finansal gelişimin başarılabilmesi için Türkiye’de ekonomik koşulların iyileştirilmesi gerekmektedir. Anahtar kelimeler: Finansal gelişim, Ekonomik büyüme, Globalleşme, Ticari Açıklık
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2020. Supervisor: Assist. Prof. Dr. Nigar Taşpınar.
Keywords: Banking and Finance; Economic Conditions and Development--Turkey; Financial development; Economic growth; Globalization; Trade openness